Prophetic Preaching in neo-Pentecostal Christianity during the socio-economic and socio-political crisis of Zimbabwe (2000- 2012) : a Practical Theological exploration - Wepener, Cas, 1972- (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2018.